Taxes and Economic Freedom: Moderating Effect of Government Effectiveness - Maryam Yousefinejad; Amilia Syuhada Binti Abdul Majid; Jaizah Othman; Noreha Halid; Muhammad Saufi Akmal Bin Roslani (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2022)
This study aims to examine the relationship between taxes and economic freedom, considering the moderating effect of government effectiveness in the Organization for Economic Cooperation and Development (OECD) countries from 1996 to 2018. The taxes are goods and services tax (GST), personal income tax (PIT), and property tax (PT). This study also examines other economic indicators such as foreign direct investment (FDI) to measure the impact of taxes on economic freedom. In this study, fixed effect panel data are used to test the hypotheses. The least squares panel results show that there is a positive and significant relationship between property tax and economic freedom. However, GST and income tax are negatively and significantly related to economic freedom. In addition, the results also demonstrate that government effectiveness moderates the relationship between taxes and economic freedom. These results can contribute to the existing literature in this area. They also allow governments to apply better tax systems to achieve a high score of economic freedom.